Assessment of Ichu Fibers Extraction and Their Use as Reinforcement in Composite Materials. Issue 5 (3rd May 2020) - Mori, S.; Tenazoa, C.; Candiotti, S.; Flores, E.; Charca, S.
ABSTRACT: This paper describes the research conducted to develop an optimal methodology to extract useful fibers from the "Ichu" grasses which can be used as reinforcement of polyester resin. Laminates were manufactured and their flexural properties were characterized as well as the optimal fiber properties. Results show that for this kind of materials, the mechanical and retting treatments are insufficient to remove lignin from the raw material state; on the other hand, alkali treatments are considerably effective. Laminates transverse strength shows an improvement (up to 30 MPa) when the alkali treatment time increases. Longitudinal strength and modulus present values around 144 MPa and 8.8 GPa respectively with fiber volume fraction around 0.38.